375 Expansion of HPV-16 specific T cells in patients with HPV-related cancers treated with bintrafusp alfa. (9th November 2020) - Toney, Nicole; Tsai, Yo-Ting; Rumfield, Claire; Pellom, Samuel; Jochems, Caroline; Strauss, Julius; Gulley, James; Schlom, Jeffrey; Donahue, Renee
Abstract : Background: The safety and efficacy of bintrafusp alfa, a first-in-class bifunctional fusion protein composed of the extracellular domain of the TGF-βRII receptor (a TGF-β 'trap') fused to a human IgG1 mAb blocking PD-L1, have been demonstrated in patients with human papillomavirus (HPV)-related cancers in an open label, multicenter phase 1 trial (NCT02517398 ), and an open-label, single center phase 2 trial (NCT03427411 ). The current study aimed to investigate whether HPV-16-specific T cells are expanded with therapy and associate with the clinical response of patients in these trials. We also present pre-clinical evidence from a mouse model of HPV-associated cancer supporting the combination of bintrafusp alfa with an HPV-16 targeted therapeutic vaccine and an immunostimulatory cytokine. Methods: Peripheral blood mononuclear cells (PBMC) were obtained from 33 patients prior to and 2 weeks after 1 and/or 3 cycles of bintrafusp alfa and evaluated for HPV-16 specific CD4+ and CD8+ T cells. PBMCs were stimulated with 15-mer peptide pools of the HPV-16 E6 and E7 oncoproteins, and T cell responses were assessed for the production of cytokines (TNFa, IFNg, IL-2) and positivity for the degranulation marker CD107a. Multifunctional T cells, positive for >2 measures, were also enumerated. For pre-clinical studies, a syngeneic mouse model of TC-1 carcinoma was treated with bintrafusp alfa alone or in combination with a liposomal-based HPV-16 therapeutic vaccine (PDS 0101) and a tumor targeting immunocytokine (NHS-muIL12) and evaluated for anti-tumor activity and immune responses. Results: HPV-16 specific T cells were increased after 1 cycle of bintrafusp alfa in a greater proportion of responders (9/14) than non-responders (4/17) (p=0.03). In addition, the magnitude of HPV-16 specific T cells was greater after 1 (p=0.04) and 3 (p<0.0001) cycles of bintrafusp alfa in responders than non-responders. Multifunctional HPV-16-specific T cells were also increased to a greater extent in responders than non-responders. Preclinical studies demonstrated that the combination of bintrafusp alfa with an HPV-16-targeted therapeutic vaccine along with an immunocytokine resulted in maximal anti-tumor activity and T cell responses. Conclusions: An early increase in HPV-16 specific T cells (after a single administration of bintrafusp alfa, prior to restaging) was associated with clinical activity in patients with HPV-related cancers undergoing bintrafusp alfa therapy. This evidence, and the pre-clinical finding of enhanced antitumor activity observed when combining bintrafusp alfa with an HPV-16 targeted vaccine and an immunostimulatory cytokine have provided the rational for an ongoing study evaluating this combination in patients with advanced HPV-associated malignancies (NCT04287868 ). Ethics Approval: All patients provided written informed consent for participation in a clinical trial that was approved by the Institutional Review Board at the National Cancer Institute (NCT02517398, NCT03427411 )